Monsoon Babies : Rainfall Shocks and Child Nutrition in Nepal - Tiwari, Sailesh (World Bank, Washington, DC, 2013)
Do household consumption-smoothing strategies in poor countries entail significant long-run costs in terms of reduced human capital? This paper exploits the timing of monsoon rainfall shocks and the seasonal nature of agriculture to isolate income effects on early childhood anthropometric outcomes in rural Nepal and to provide evidence on the persistence of these effects into later childhood. Findings suggest that a 10 percent increase in rainfall from historic norms during the most recently completed monsoon leads to a 0.15 standard deviation increase in weight-for-age for children ages 0-36 months. This total impact consists of a negative "disease environment effect" of no more than 0.02 standard deviations and a positive "income effect" as high as 0.17 standard deviations. Consistent with this interpretation, excess monsoon rainfall also enhances child stature, but only if the monsoon rainfall shock is experienced in the second year of life. Moreover, this effect on child height is transitory, dissipating completely by age five.